Proceedings of the 15th Annual Conference on Genetic and Evolutionary Computation 2013
DOI: 10.1145/2463372.2463569
|View full text |Cite
|
Sign up to set email alerts
|

How the (1+λ) evolutionary algorithm optimizes linear functions

Abstract: We analyze how the (1 + λ) evolutionary algorithm (EA) optimizes linear pseudo-Boolean functions. We prove that it finds the optimum of any linear function within an expected number of O( 1 λ n log n + n) iterations. We also show that this bound is sharp for some functions, e.g., the binary value function. Hence unlike for the (1 + 1) EA, for the (1 + λ) EA different linear functions may have run-times of different asymptotic order. The proof of our upper bound heavily relies on a number of classic and recent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 35 publications
(65 reference statements)
0
6
0
Order By: Relevance
“…, and by applying Wald's equation [9,20], using E (X j ) to denote an upper bound on all E (X j,k ) in stage j:…”
Section: Generalised Mechanismsmentioning
confidence: 99%
“…, and by applying Wald's equation [9,20], using E (X j ) to denote an upper bound on all E (X j,k ) in stage j:…”
Section: Generalised Mechanismsmentioning
confidence: 99%
“…Lemma 5 (extension of Wald's equation from [6]). Let T be a random variable with bounded expectation and let X1, X2, .…”
Section: Proof Of Theoremmentioning
confidence: 99%
“…Rowe and Sudholt [17] discussed the running time of (1 + λ) EAs in terms of the offspring population size on unimodal functions. Doerr and Künnemann [18] analysed the time bound of (1 + λ) EAs for optimizing linear pseudo-Boolean functions. Doerr and Künnemann [19] showed that (1 + λ) EAs with even very large offspring populations does not reduce the runtime significantly on the Royal Road function.…”
Section: Introductionmentioning
confidence: 99%